2008
DOI: 10.1016/j.berh.2007.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Fibrodysplasia ossificans progressiva

Abstract: Fibrodysplasia ossificans progressiva (FOP), a rare and disabling genetic condition of congenital skeletal malformations and progressive heterotopic ossification (HO), is the most catastrophic disorder of HO in humans. Episodic disease flare-ups are precipitated by soft tissue injury, and immobility is cumulative. Recently, a recurrent mutation in activin receptor IA/activin-like kinase 2 (ACVR1/ALK2), a bone morphogenetic protein (BMP) type I receptor, was reported in all sporadic and familial cases of classi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
374
1
19

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 312 publications
(420 citation statements)
references
References 55 publications
4
374
1
19
Order By: Relevance
“…Individuals with FOP appear normal at birth except for the characteristic malformation of the great toes (3,4,10,11) , which was noticed by the parents of the girl reported in the present study, but they did not pay much attention to this, since it did not cause functional changes. As for treatment, there are anecdotal reports on the efficacy of corticoids in limiting inflammation and progression of heterotopic ossification during flare-ups, which means that if prednisone is administered at a 2mg/Kg/d dose during 4 days, starting within the first 24 hours after the flare-up, the intense inflammation and tissular edema observed in the first stages of ossification will be reduced.…”
Section: Discussioncontrasting
confidence: 53%
See 4 more Smart Citations
“…Individuals with FOP appear normal at birth except for the characteristic malformation of the great toes (3,4,10,11) , which was noticed by the parents of the girl reported in the present study, but they did not pay much attention to this, since it did not cause functional changes. As for treatment, there are anecdotal reports on the efficacy of corticoids in limiting inflammation and progression of heterotopic ossification during flare-ups, which means that if prednisone is administered at a 2mg/Kg/d dose during 4 days, starting within the first 24 hours after the flare-up, the intense inflammation and tissular edema observed in the first stages of ossification will be reduced.…”
Section: Discussioncontrasting
confidence: 53%
“…This mutation causes a deregulation of the bone morphogenetic protein signaling pathway (7,8) . Previous studies have demonstrated that there was no ethnic, racial, gender or geographic predisposition for the development of the disease (3,4) . It is known that both genetic and environmental factors determine FOP phenotype, the first during prenatal development and the latter in the progression of heterotopic ossifications (5,7,8) .…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations